2015
DOI: 10.3168/jds.2014-9266
|View full text |Cite
|
Sign up to set email alerts
|

Experienced and inexperienced observers achieved relatively high within-observer agreement on video mobility scoring of dairy cows

Abstract: Assessment of lameness prevalence and severity requires visual evaluation of thelocomotion of a cow. Welfare schemes including locomotion assessments are increasingly being adopted, and more farmers and their veterinarians might implement a locomotion-scoring routine together. However, high within-observer agreement is a prerequisite for obtaining valid mobility scorings, and within-observer agreement cannot be estimated in a barn, because the gait of cows is dynamic and may change between 2 occasions. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…In such case, the expected inter-observer agreement would be 0.64 (0.80 times 0.80) illustrating the fact that a low intra-observer agreement for even just one rater would inevitably lead to a lower inter-observer agreement. Although intra-observer agreement could not be estimated in the current study, the findings of Garcia et al (2015) suggest that it would be greater than the observed inter-observer agreement value. The high inter-observer agreements observed in both exams of the present study suggest higher intra-observer agreement.…”
Section: Short Communication: An Observational Study Investigating In...contrasting
confidence: 73%
See 1 more Smart Citation
“…In such case, the expected inter-observer agreement would be 0.64 (0.80 times 0.80) illustrating the fact that a low intra-observer agreement for even just one rater would inevitably lead to a lower inter-observer agreement. Although intra-observer agreement could not be estimated in the current study, the findings of Garcia et al (2015) suggest that it would be greater than the observed inter-observer agreement value. The high inter-observer agreements observed in both exams of the present study suggest higher intra-observer agreement.…”
Section: Short Communication: An Observational Study Investigating In...contrasting
confidence: 73%
“…For practical reasons, and because the aim of the current study was inter-observer agreement, repeated BCS measurements within the same observers were not collected and intra-observer agreement could not be computed. As suggested by Garcia et al (2015), before computing inter-observer agreement, the first step in a validation process should be the assessment of the intra-observer agreement to evaluate if observers agree at least with themselves. The latter study gave an example where 2 observers using a categorical scale have intra-observer agreement of 0.80.…”
Section: Short Communication: An Observational Study Investigating In...mentioning
confidence: 99%
“…Combining this with the difficulties expressed by farmers in terms of identification of lame animals suggests that training and practice is required in order to enable farmers to improve the prompt detection of lame animals. Although some dairy cattle studies have suggested that training may provide limited improvements in intra- and inter-observer agreement when locomotion scoring (26, 27), inter-observer reliability has been shown to increase with increased time/scoring sessions (28). Also, experienced scorers have been shown to perform better than less experiences scorers when using video footage of cattle (29).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that indicators for on-farm assessments can successfully be trained using pictures for body condition scoring (BCS) in dairy cows (Ferguson et al, 2006) and in goats (Vieira et al, 2015). The same applies to lameness in dairy cows by using videos (Garcia et al, 2015). However, information on training for farmers is lacking.…”
Section: Introductionmentioning
confidence: 99%